Three-Dimensional Numerical Investigation of Nanofluids Flow in Microtube with Different Values of Heat Flux - Salman B.H.; Mohammed H.A.; Munisamy K.M.; Kherbeet A.S. (John Wiley and Sons Inc, 2023)
Alumina; Aluminum oxide; Copper oxides; Ethylene; Ethylene glycol; Forced convection; Heat transfer; II-VI semiconductors; Laminar flow; Nanofluidics; Nanoparticles; Oxide minerals; Reynolds number; Silica; Silicon; SiO2 nanoparticles; Volume fraction; Zinc oxide; Heat transfer augmentation; Microtube; Nanofluids; Nanoparticle sizes; Numerical investigations; Heat flux